Associations of prenatal environmental phenol and phthalate biomarkers with respiratory and allergic diseases among children aged 6 and 7 years. (June 2018) - Buckley, Jessie P.; Quirós-Alcalá, Lesliam; Teitelbaum, Susan L.; Calafat, Antonia M.; Wolff, Mary S.; Engel, Stephanie M.
Abstract: Background: Prenatal environmental phenol and phthalate exposures may alter immune or inflammatory responses leading to respiratory and allergic disease. Objectives: We estimated associations of prenatal environmental phenol and phthalate biomarkers with respiratory and allergic outcomes among children in the Mount Sinai Children's Environmental Health Study. Methods: We quantified urinary biomarkers of benzophenone-3, bisphenol A, paradichlorobenzene (as 2, 5-dichlorophenol), triclosan, and 10 phthalate metabolites in third trimester maternal samples and assessed asthma, wheeze, and atopic skin conditions via parent questionnaires at ages 6 and 7 years ( n = 164 children with 240 observations). We used logistic regression to estimate covariate-adjusted odds ratios (ORs) and 95% confidence intervals (CIs) per standard deviation difference in natural log biomarker concentrations and examined effect measure modification by child's sex. Results: Associations of prenatal 2, 5-dichlorophenol (all outcomes) and bisphenol A (asthma outcomes) were modified by child's sex, with increased odds of outcomes among boys but not girls. Among boys, ORs for asthma diagnosis per standard deviation difference in biomarker concentration were 3.00 (95% CI: 1.36, 6.59) for 2, 5-dichlorophenol and 3.04 (95% CI: 1.38, 6.68) for bisphenol A. Wheeze in the past 12 months was inversely associated with low molecular weight phthalate metabolites among girls only (OR: 0.27, 95% CI: 0.13, 0.59) and with benzophenone-3 among all children (OR: 0.65, 95% CI: 0.44, 0.96). Conclusions: Prenatal bisphenol A and paradichlorobenzene exposures were associated with pediatric respiratory outcomes among boys. Future studies may shed light on biological mechanisms and potential sexually-dimorphic effects of select phenols and phthalates on respiratory disease development. Highlights: Measured urinary phenol and phthalate biomarkers in the third trimester of pregnancy Assessed asthma, wheeze, and atopic skin conditions by questionnaire 2, 5 dichlorophenol and bisphenol A (boys only) positively associated with outcomes Benzophenone-3 and select phthalates (girls only) inversely associated with wheeze Prenatal chemical exposures may have sex-dependent effects on respiratory health